Defining trajectories in older adults with back pain presenting in general practice. (2nd November 2016) - Enthoven, Wendy T. M.; Koes, Bart W.; Bierma-Zeinstra, Sita M. A; Bueving, Herman J.; Bohnen, Arthur M.; Peul, Wilco C.; van Tulder, Maurits W.; Berger, Marjolein Y.; Luijsterburg, Pim A. J.
Abstract : Background: although back pain is a frequently recurring disorder, the course of back pain remains uncertain. Therefore, this study aimed to identify different trajectories in older adults with back pain who presented in general practice and to determine which baseline characteristics are associated with these trajectories. Methods: the BACE study is a prospective cohort study including 675 patients (aged >55 years) with back pain who consulted a general practitioner; patients were followed for 3 years. Latent class growth analysis was used to identify different trajectories in back pain severity measured at eight different time points. A multinomial regression analysis was used to assess variables associated with membership of an identified trajectory. Results: using the different indices of fit and the usefulness of the different trajectories in clinical practice, a 3-class cubic model was determined to be the best model. The three trajectories were defined as 'low pain trajectory', 'high pain trajectory' and 'intermediate pain trajectory'. Baseline variables associated with a higher chance of being in the intermediate or high trajectory were: female gender, higher body mass index, chronic back pain, more disability, lower scores on the SF-36 physical summary scale, and negative expectations of recovery. Conclusions: three different back pain trajectories were identified in older adults presenting with back pain in general practice. Various baseline characteristics were associated with a higher chance of being in the high or intermediate back pain trajectory. These characteristics might help identify patients at risk for a less favourable outcome.